If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = -4(x + -1) Reorder the terms: 4 = -4(-1 + x) 4 = (-1 * -4 + x * -4) 4 = (4 + -4x) Add '-4' to each side of the equation. 4 + -4 = 4 + -4 + -4x Combine like terms: 4 + -4 = 0 0 = 4 + -4 + -4x Combine like terms: 4 + -4 = 0 0 = 0 + -4x 0 = -4x Solving 0 = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 0 + 4x = -4x + 4x Remove the zero: 4x = -4x + 4x Combine like terms: -4x + 4x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| 27x+12y-2561=0 | | -12x-15=-123 | | -8+(-4)+5= | | 100+(-30)= | | 88x^2-97x+24=0 | | 88x^2-97+24=0 | | -15+-6= | | 3g+4(-6g+3g)=1-g | | 3(4C-1)-16=10C+3 | | .25(4x+10)=8 | | 18+5T=-3N-12 | | 8y-8=35-7y | | 3y+4+10y-17=14-23y+16-7y | | -5N+10=-3N-12 | | 6y+7-19=7y+13-3y-21 | | A(x-1)-bx=0 | | 8X+58=8X+14 | | -10z+75=-5 | | 2x-10i=8-(4iy) | | 4-C=25 | | 8X+8=5X+7 | | 9*x*x*x+6*x*x=0 | | 15+4y=y | | 125-3x=24+23x | | 2x-10i=8-(4y)I | | 27-18=3(X-3) | | 12-8x=123-43x | | -127-8x=-68-10x | | 28+3Y-6=13Y-13-3Y | | 5x+3=27-4x | | 6x+21=5x-51 | | x+19+3x=-15-3x-22 |